REVIEW ARTICLE: GAMBARAN GAYA HIDUP MASYARAKAT PESISIR TERHADAP PENYAKIT HIPERTENSI - Kiara Aulia Pelawi (Jurnal Kesehatan, 2024)
Hypertension is an increase in blood pressure inside the arteries. In general, hypertension is an asymptomatic condition where abnormal blood pressure high in the arteries can cause an increased risk of stroke, heart failure aneurysm, heart attack and kidney damage. This study uses the literature review research method where this method is carried out by comparing research methods, data processing methods and research results that have been found in the article. The selected journal reference is with journals published in 2019-2022. Data collection will be carried out around October- November 2022. Based on the results of research and discussion obtained, there is a lifestyle relationship with hypertension in coastal communities. Therefore, people must pay more attention to lifestyle to avoid hypertension.